2021
DOI: 10.1186/s40066-020-00278-2
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of improved agricultural technology and its impact on household income: a propensity score matching estimation in eastern Ethiopia

Abstract: Background Adoption of improved agricultural technologies remains to be a promising strategy to achieve food security and poverty reduction in many developing countries. However, there are limited rigorous impact evaluations on the contributions of such technologies on household welfare. This paper investigates the impact of improved agricultural technology use on farm household income in eastern Ethiopia. Methods Primary data for the study was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 48 publications
8
34
0
2
Order By: Relevance
“…Hence, various studies conducted around the world and in Ethiopia have suggested that agricultural technologies have the capability of reducing poverty in large scale. For example, the adoption of alternative farming technologies has been found to significantly increase yields, increase farm income, increase household consumption, improve nutrition, and generally improves household welfare ( Sebsibie et al., 2015 ; Hagos, 2016 ; Tesfaye et al., 2016 ; Alwang et al., 2017; Belete and Melak, 2018 ; Akinrinola and Adeyemo, 2018 ; Adebayo et al., 2018 ; Ahmed and Anang., 2019 ; Verkaart et al., 2019 ; Natnael, 2019 ; Legesse et al., 2019 ; Tesfay, 2020 ; Biru et al., 2020 ; Teka and Lee, 2020 ; Abewa et al., 2020 ; Ayenew et al., 2020 ; Shita et al., 2020 ; Belay and Mengiste, 2021 ; Habtewold, 2021 ; Wordofa et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, various studies conducted around the world and in Ethiopia have suggested that agricultural technologies have the capability of reducing poverty in large scale. For example, the adoption of alternative farming technologies has been found to significantly increase yields, increase farm income, increase household consumption, improve nutrition, and generally improves household welfare ( Sebsibie et al., 2015 ; Hagos, 2016 ; Tesfaye et al., 2016 ; Alwang et al., 2017; Belete and Melak, 2018 ; Akinrinola and Adeyemo, 2018 ; Adebayo et al., 2018 ; Ahmed and Anang., 2019 ; Verkaart et al., 2019 ; Natnael, 2019 ; Legesse et al., 2019 ; Tesfay, 2020 ; Biru et al., 2020 ; Teka and Lee, 2020 ; Abewa et al., 2020 ; Ayenew et al., 2020 ; Shita et al., 2020 ; Belay and Mengiste, 2021 ; Habtewold, 2021 ; Wordofa et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2020) used chemical fertilizers and improved seeds for Ethiopia, Abewa et al. (2020) used the Teff variety for Ethiopia and Wordofa et al. (2021) used improved livestock and crop technologies for Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Debido al constante requerimiento de alimento para el pastoreo y las características cultivables de la tierra, los productores demandan tecnologías relacionadas a la agricultura como segunda preferencia: maquinaria agrícola y riego tecnificado, que les permitan desarrollar actividades económicas sostenibles y de subsistencia. Junto a las demandas identificadas se expresa que estos productores necesitan de conocimientos tecnológicos para dar eficiencia a su sistema de producción en perspectiva del desarrollo sostenible, opiniones concordantes con los estudios de (Bedoya Justo & Julca Otiniano, 2021;De La Cruz S. & Dessein, 2021;Valarezo et al, 2020;Wordofa et al, 2021).…”
Section: Demanda Social De Tecnologías Agropecuariasunclassified
“…), organic and inorganic fertilizers are among the main improved agricultural technologies mainly practiced by smallholder farmers in Ethiopia. The adoption of either of the abovementioned improved agricultural technologies revealed a positive effect on productivity (6)(7)(8) and farmers' welfare (9)(10)(11) . Also, effective improved agricultural production technologies enhance marketable surplus production by smallholders (12) .…”
Section: Introductionmentioning
confidence: 99%